Emergence of mcr-1-Harboring Salmonella enterica Serovar Sinstorf Type ST155 Isolated From Patients With Diarrhea in Jiangsu, China - Liu, Guoye; Qian, Huimin; Lv, Jingwen; Tian, Benshun; Bao, Changjun; Yan, Hong; Gu, Bing (Frontiers in Microbiology, 2021)
Background: This study analysed the antimicrobial resistance phenotypes and mechanisms of quinolone, cephalosporins and colistin resistance in nontyphoidal Salmonella from patients with diarrhoea in Jiangsu, China. Methods: A total of 741 nontyphoidal Salmonella isolates were collected from hospitals in major cities of Jiangsu Province, China between 2016 and 2017. Their susceptibility to commonly used antibiotics was evaluated by broth micro-dilution and sequencing analysis of resistance genes screened by a PCR method. For mcr-1 positive isolates, genetic relationship study was carried out by pulsed-field gel electrophoresis and multiloci sequence typing analysis. The transferability of these plasmids was measured with conjugation experiments and the genetic locations of mcr-1 were analysed by pulsed-field gel electrophoresis profiles of S1-digested genomic DNA and subsequent Southern blot hybridization. Results: Among 741 nontyphoidal Salmonella isolates, the most common serotypes identified were S. typhimurium (n = 257, 34.7%) and S. enteritidis (n = 127, 17.1%), and the isolates showed 21.7%, 20.6%, and 5.0% resistance to cephalosporins, ciprofloxacin, and colistin, respectively. Among the 335 nalidixic acid-resistant Salmonella, 213 (63.6%) and 45 (13.4%) had at least one mutation in gyrA and parC. Among the plasmid-mediated resistance, qnrS1 (85; 41.9%) and aac(6’)-Ib-cr4 (75; 36.9%) were the most common quinolone resistance (PMQR) genes, while blaCTX-M-14 (n = 35) and blaCTX-M-55 (n = 46) were found to be dominant extended-spectrum beta-lactamase (ESBL) genes in nontyphoidal Salmonella. In addition, 8 mcr-1-harboring strains were detected since 2016 and they were predominate in children under the age of 7 years. Conjugation assays showed the donor Salmonella strain has functional and transferable colistin resistance and Southern blot hybridization revealed that mcr-1 was located in a high molecular weight plasmid. Conclusion: In nontyphoidal Salmonella, there is a rapidly increasing trend of colistin resistance and this is the first report of patients harbouring mcr-1-positive Salmonella with a new ST type ST155 and new serotype S. Sinstorf. These findings demonstrate the necessity for cautious use and the continuous monitoring of colistin in clinical applications.